Accelerated Action for Food Systems Resilience: Egypt’s plans for COP27 and the role of CGIAR: Video - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
Unprecedented extreme weather events linked to climate change are contributing to the current global food and energy price crisis and severely impacting livelihoods and food and nutrition security. In this context, expectations are high for the 27th Conference of the Parties of the U.N. Framework Convention on Climate Change (COP27) taking place under the Presidency of the Arab Republic of Egypt.